STRUCTURAL ANALYSIS FOR A NANO-CRYSTALLINE FILM (ZnS) BY AEROSOL SPRAY PYROLYSIS TECHNIQUE - Shehu, Muhammad Shafiu; Lawal, Rasheed Segun; Ibrahim, Nura; Yunusa, Nuhu; A.O, Olaoye; Adinoyi, Siyaku (FUDMA JOURNAL OF SCIENCES, 2023)
Nano thin film materials play an indispensable role in modern electronics and other field of material sciences especially in a photovoltaic technology. The scope of this research is to grow Zinc Sulphide (ZnS) thin film and characterize structurally to understand the benefits of the study choosing chemical deposition method (The aerosol spray pyrolysis), the chemical combination analysis and the annealing temperature. Specifically on the film strength and its applications. In the light of this work, Nano crystalline ZnS thin films was grown by carefully dissolving 1.48g of Zinc Acetate (Zn(CH3CO2)2) in 15ml of a distilled water (H2O), Followed by the deposition of 50, 5, and 30ml of acetone (CH3COCH3), acetic acid (CH3COOH) and ethanol (C2H6O) to the solution respectively, all in molar concentration of 0.1 M per ml. The solution was allowed to spray for 10 minutes on a soda lime glass substrate (SLG) at 300oC. The process was repeated for the sample annealed at 300oC and 400oC under Nitrogen gas (N2) environment for 60 minutes. The X-ray diffraction pattern of all the films deposited shows a cubic crystal type with mean crystallite size in the range 0.35nm as deposited, 0.4179 nm and 0.44nm at 300oC and 400oC annealing temperature respectively. Patterns of the sprayed film after performing the phase analysis reveal peaks corresponding to the (111) planes of reflection, which indicate the suitability of the deposition process and chemical combination. Furthermore, it is also concluded that the strength of the material depends on the annealing and substrate temperature.